Net atrioventricular compliance is an independent predictor of cardiovascular death in mitral stenosis. Issue 23 (5th August 2017) - Nunes, Maria Carmo Pereira; Tan, Timothy C; Elmariah, Sammy; Lodi-Junqueira, Lucas; Nascimento, Bruno Ramos; do Lago, Rodrigo; Padilha da Silva, Jose Luiz; Reis, Rodrigo Citton Padilha; Zeng, Xin; Palacios, Igor F; Hung, Judy; Levine, Robert A
Abstract : Objectives: Rheumatic mitral stenosis (MS) is a progressive disease, and risk of death may persist despite relief of the obstruction. Net atrioventricular compliance (Cn ) modulates the overall haemodynamic burden of the MS and may be useful in predicting cardiovascular death after percutaneous mitral valvuloplasty (PMV). Methods: A total of 427 patients (mean age 50±16 years, 84% female) with severe MS undergoing PMV were enrolled. Doppler-derived Cn was estimated at baseline using a previously validated equation. The primary endpoint was late cardiovascular death, and the secondary endpoint was a composite of all-cause mortality, mitral valve (MV) replacement or repeat PMV over a median follow-up of 31 months (IQR: 7.8–49.2 months). Results: At baseline, 209 patients (49%) were in New York Heart Association (NYHA) functional class III or IV. During follow-up, 49 patients died (41 cardiovascular deaths), 50 underwent MV replacement and 12 required repeat PMV, with an overall incidence of cardiac mortality and adverse events of 4.1 deaths and 11.1 events per 100 patient-years, respectively. Low baseline Cn was a strong predictor of both cardiac death (adjusted HR 0.70, 95% CI 0.49 to 0.86) and composite endpoint (adjusted HR 0.81, 95% CI 0.67 to 0.91) after adjusting for clinical factors, baseline pulmonary artery pressure, tricuspid regurgitation severity, right ventricular function and immediate procedural haemodynamic data. The inclusion of Cn in a model with conventional parameters resulted in improvement in 5-year cardiovascular mortality risk prediction. Conclusions: Baseline Cn is a strong predictor of cardiovascular death in patients with MS undergoing PMV, independent of other prognostic markers of decreased survival in MS, including baseline patient characteristics and postprocedural data. Cn assessment therefore has potential value in evaluation of cardiovascular mortality risk in the setting of MS.